The relationship between urbanization and agricultural areas in the Aegean region of Turkey - Nurlu E.; Erdem U. (Interdependency between agriculture and urbanization: Conflicts on sustainable use of soil and water, 2001)
From the ancient period till now, coastal areas have always been most popular living areas. Coastal zone of Aegean Region, which covers nearly 2800 km from Maritza River to Dalaman Stream, has been in an important situation for the mankind because of its natural and cultural conditions. This zone is facing many problems resulting from population explosion. Suitable climatic conditions, productive agricultural lands, touristic resorts and good working conditions are the main reasons for this explosion. During this process usually large natural lands as well as fertile agricultural ones were transformed into an urban land. Therefore agricultural lands have gradually decreased day after day. Unfortunately, these applications effected Meander and Great Meander Basins just like the other basins of the Aegean Coastal zone. The current presentation discusses this situation with case studies from the center of Aydin Province, Soke and Kusadasi districts, in the light of studies undertaken during the last decade in these basins.
Seminar: Interdependency between Agriculture and Urbanization: Conflicts on Sustainable Use of Soil and Water, 2000/04/02-06, Tunis (Tunisia)